Mapping the nucleolar proteome reveals a spatiotemporal organization related to intrinsic protein disorder. Issue 8 (3rd August 2020) - Stenström, Lovisa; Mahdessian, Diana; Gnann, Christian; Cesnik, Anthony J; Ouyang, Wei; Leonetti, Manuel D; Uhlén, Mathias; Cuylen‐Haering, Sara; Thul, Peter J; Lundberg, Emma
Abstract: The nucleolus is essential for ribosome biogenesis and is involved in many other cellular functions. We performed a systematic spatiotemporal dissection of the human nucleolar proteome using confocal microscopy. In total, 1, 318 nucleolar proteins were identified; 287 were localized to fibrillar components, and 157 were enriched along the nucleoplasmic border, indicating a potential fourth nucleolar subcompartment: the nucleoli rim. We found 65 nucleolar proteins (36 uncharacterized) to relocate to the chromosomal periphery during mitosis. Interestingly, we observed temporal partitioning into two recruitment phenotypes: early (prometaphase) and late (after metaphase), suggesting phase‐specific functions. We further show that the expression of MKI67 is critical for this temporal partitioning. We provide the first proteome‐wide analysis of intrinsic protein disorder for the human nucleolus and show that nucleolar proteins in general, and mitotic chromosome proteins in particular, have significantly higher intrinsic disorder level compared to cytosolic proteins. In summary, this study provides a comprehensive and essential resource of spatiotemporal expression data for the nucleolar proteome as part of the Human Protein Atlas. Synopsis: Spatiotemporal characterization of the human nucleolar proteome reveals spatial partitioning into fibrillar components and nucleoli rim. A subset of proteins with high intrinsic disorder show temporal relocation to the chromosomal periphery during mitosis. The human nucleolar proteome is large and functionally diverse with precise partitioning in time and space. The nucleolus rim is a subcompartment with a distinct proteomic composition. 65 nucleolar proteins (36 uncharacterized), many with high intrinsic disorder, relocate to the chromosomal periphery during mitosis. The recruitment of proteins to the chromosomal periphery is dependent on MKI67 and is partitioned into two phenotypes: early (prometaphase) and late (after metaphase) recruitment, suggesting phase‐specific functions. Abstract : Spatiotemporal characterization of the human nucleolar proteome reveals spatial partitioning into fibrillar components and nucleoli rim. A subset of proteins with high intrinsic disorder show temporal relocation to the chromosomal periphery during mitosis.